Finite Element Approach of Shielded, Suspended and Inverted Microstrip Lines - Sarhan Musa; Matthew N.O. Sadiku (Bulletin of Electrical Engineering and Informatics, 2013)
In this paper, we present finite element method (FEM) to investigate the electromagnetic analysis of two-dimensional (2D) shielded, suspended and inverted microstrip lines for microwave applications.  In the proposed method, we specifically determine the values of capacitance per unit length, inductance per unit length, and characteristic impedance of the microstrip lines. Extensive simulation results are presented and some comparative results are given with other methods and found them to be in excellent agreement. We extend the analysis by designing our new model of shielded, inverted microstrip lines and compared it with shielded, suspended microstrip lines; we found them to be very close. Also, we determine the quasi-TEM spectral for the potential distribution of these microstrip lines.